2018
DOI: 10.1007/s10517-018-4236-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Cardioprotective Action of σ1 Receptor Agonist Anxiolytic Fabomotizole Hydrochloride (Afobazole)

Abstract: Original translational rat model of chronic heart failure provoked by experimental anterior transmural myocardium infarction was employed to examine the preventive action of anxiolytic Afobazole (15 mg/kg/day administered intraperitoneally during the first 15 days after coronary occlusion) on the development of the heart failure assessed in 3 months after infarction. Afobazole prevented the development of pathologic remodeling of the myocardium, maintained its inotropic function, and decreased the plasma level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Another study also showed delayed cardioprotective effects of afobazole, evaluated by using echocardiography in an experim ental myocardial infarction model (rat model of acute myocardial ischemia) (Kryzhanovskii et al, 2017). It has been proposed that the cardiotropic effects of the anxiolytic afobazole were associated with Sigmar1 agonistic effects in cardiomyocytes (Kryzhanovskii et al, 2017(Kryzhanovskii et al, , 2018. However, a recent study showed that chronic Sigmar1 activation ameliorated ventricular remodeling and decreased susceptibility to ventricular arrhythmias after myocardial infarction in rats (Fo et al, 2020).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also showed delayed cardioprotective effects of afobazole, evaluated by using echocardiography in an experim ental myocardial infarction model (rat model of acute myocardial ischemia) (Kryzhanovskii et al, 2017). It has been proposed that the cardiotropic effects of the anxiolytic afobazole were associated with Sigmar1 agonistic effects in cardiomyocytes (Kryzhanovskii et al, 2017(Kryzhanovskii et al, , 2018. However, a recent study showed that chronic Sigmar1 activation ameliorated ventricular remodeling and decreased susceptibility to ventricular arrhythmias after myocardial infarction in rats (Fo et al, 2020).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Treatment with Sigmar1 ligand afobazole prevented the development of pathologic remodeling of the myocardium, maintained its inotropic function, and decreased the plasma level of brain natriuretic peptide in a rat model of myocardial infarction. Interestingly, afobazole treatment down-regulated the mRNA expression of angiotensin, vasopressin, glucocorticoid receptor, and Epac2 protein level in the infarcted myocardium ( Kryzhanovskii et al, 2018 ). Another study also showed delayed cardioprotective effects of afobazole, evaluated by using echocardiography in an experim ental myocardial infarction model (rat model of acute myocardial ischemia) ( Kryzhanovskii et al, 2017 ).…”
Section: Physiological and Pathological Role Of Sigmar1mentioning
confidence: 99%